Stem Cells as a Tool to Improve Outcomes of Islet Transplantation. (30th August 2012) - Sims, Emily; Evans-Molina, Carmella
Abstract : The publication of the promising results of the Edmonton protocol in 2000 generated optimism for islet transplantation as a potential cure for Type 1 Diabetes Mellitus. Unfortunately, follow-up data revealed that less than 10% of patients achieved long-term insulin independence. More recent data from other large trials like the Collaborative Islet Transplant Registry show incremental improvement with 44% of islet transplant recipients maintaining insulin independence at three years of follow-up. Multiple underlying issues have been identified that contribute to islet graft failure, and newer research has attempted to address these problems. Stem cells have been utilized not only as a functional replacement for β cells, but also as companion or supportive cells to address a variety of different obstacles that prevent ideal graft viability and function. In this paper, we outline the manners in which stem cells have been applied to address barriers to the achievement of long-term insulin independence following islet transplantation.